2002
DOI: 10.1038/sj.bmt.1703312
|View full text |Cite
|
Sign up to set email alerts
|

Renal function after autologous bone marrow transplantation in children: a long-term prospective study

Abstract: Summary:We measured glomerular filtration rate (GFR), effective renal plasma flow (ERPF) and the concentrating capacity of the kidneys in children after autologous BMT. Twenty-six patients had received TBI in their conditioning regimen and 14 patients had received chemotherapy only. Median follow-up was 10 years. Mean After this initial decrease, GFR and ERPF remained essentially unchanged in both groups. The mean concentrating capacity of the kidneys was normal before and after BMT. In seven patients chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 33 publications
4
70
3
2
Order By: Relevance
“…13,14 CRF post-HSCT in children as well as in adults has predominantly been associated with TBI. 11,13,[15][16][17][18][19][20][21][22][23] Nevertheless, in accordance with our previous studies 1-year post-HSCT, in the present study we did not find a relation between TBI/TAI and development of CRF. 4,5 The irradiation dose in our study was slightly different (4-8 Gy in one fraction or 12 Gy in two fractions, Table 1) compared to other pediatric studies: 10 Gy in one fraction, 2,19 12-14 Gy in 6-8 fractions 15 and 13 Gy in eight fractions.…”
Section: Glomerular Functionsupporting
confidence: 79%
“…13,14 CRF post-HSCT in children as well as in adults has predominantly been associated with TBI. 11,13,[15][16][17][18][19][20][21][22][23] Nevertheless, in accordance with our previous studies 1-year post-HSCT, in the present study we did not find a relation between TBI/TAI and development of CRF. 4,5 The irradiation dose in our study was slightly different (4-8 Gy in one fraction or 12 Gy in two fractions, Table 1) compared to other pediatric studies: 10 Gy in one fraction, 2,19 12-14 Gy in 6-8 fractions 15 and 13 Gy in eight fractions.…”
Section: Glomerular Functionsupporting
confidence: 79%
“…Besides these agents, high-dose methotrexate and cyclophosphamide are known for their acute nephrotoxicity, but evidence regarding their long-term effects is lacking (11). Additionally, kidney surgery and radiation therapy may cause renal impairments, such as hyperfiltration or radiation nephropathy, characterized by hypertension, decline in GFR, and proteinuria (12)(13)(14). The long-term effect of radiation nephropathy and hypertension have not been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Although exposure of kidneys to radiation during hematopoietic cell transplantation has been hypothesized as a risk factor for bone marrow transplant nephropathy, studies have shown conflicting data regarding renal shielding and long-term renal insufficiency. 5,[8][9][10][11][12] Other causes of thrombotic microangiopathy must be considered in hematopoietic cell transplant recipients, including exacerbation of endothelial injury by chemotherapy, immune-mediated injury, and perhaps most notably, cyclosporine inhibitor toxicity, given as prophylaxis or treatment for graft-versus-host disease.…”
mentioning
confidence: 99%